Seed treatment with macroalgal-derived fucoidan and nanohydroxyapatite mitigates Fusarium falciforme ASU26 infection in faba bean: insights from morphological, physiological, anatomical, and FT-IR analyses - Mohamed Gomaa; Eman S. E. Aldaby; Ghada Abd-Elmonsef Mahmoud (BMC Plant Biology)
Abstract Background Soil-borne diseases are becoming more prevalent due to climate change, while the use of pesticides is being discouraged due to their harmful environmental impacts. This study explored the potential of natural compounds, specifically fucoidan from brown seaweed and nanohydroxyapatite from calcareous red seaweed, as eco-friendly alternatives for mitigating Fusarium infections. The treatments aimed to enhance the plant’s defense mechanisms and improve seedling growth. Results The treatments using fucoidan, nanohydroxyapatite, or their combination at concentrations of 250–500 µg mL⁻¹ for 6 h, significantly enhanced seedling growth, including increased height, root area, and both fresh and dry weights. Photosynthetic pigment levels and total flavonoid contents increased by more than 30% in treated seedlings compared to the infected control. Malondialdehyde levels, an indicator of oxidative stress, were notably reduced, comparable to or lower than those in the non-infected control. Enzymatic activities associated with plant defense, such as chitinase and polyphenol oxidase, were also higher in treated seedlings. Anatomical improvements were observed, including enhanced vascular cylinder and metaxylem areas. FT-IR analyses highlighted several biochemical changes, such as an increased CH₂/CH₃ ratio indicating lipid structural variation, reduced amide I and II bands, an increase in the C = C band (linked to lignin), and a higher degree of esterification compared to infected controls. Conclusions The study demonstrates that fucoidan and nanohydroxyapatite are promising sustainable, cost-effective, and environmentally friendly treatments that effectively boost the defense responses and growth of faba bean seedlings against Fusarium falciforme ASU26 infection. These natural compounds could serve as alternatives to conventional pesticides, offering enhanced plant resistance to pathogens and supporting healthier plant growth. Clinical trial number Not applicable.